AN IDENTIFICATION OF COST MANAGEMENT CHALLENGES IN PUBLIC SECTOR PROJECTS - T.G MONYANE; Fidelise EMUZE; G CRAFFORD (Journal of Construction Project Management and Innovation)
The prevalence of cost overruns in public sector projects is a call to all stakeholders to address cost management issues in the construction industry. This study seeks to make sense of these existing cost management practices. Such sense-making will enable an evaluation of the status quo, and it will identify challenges hindering effective cost management during project delivery. Adopting a qualitative case study research design, this study relies on data obtained from a purposively selected list of interviewees from a cluster of cases, i.e., recently completed public sector construction projects in the Free State. These interviews will be juxtaposed with evidence from project-related documents. Based on the data, the study will provide a profile of existing cost management frameworks applied to these projects. Encompassing various stages of the project delivery life cycle, this profile will enable an identification of the challenges in terms of cost management on these projects. It is expected that findings from this study will provide an outline of the failings of current cost management frameworks.